2001
DOI: 10.1084/jem.193.7.855
|View full text |Cite
|
Sign up to set email alerts
|

Cd47-Signal Regulatory Protein α (Sirpα) Regulates Fcγ and Complement Receptor–Mediated Phagocytosis

Abstract: In autoimmune hemolytic anemia (AIHA), circulating red blood cells (RBCs) opsonized with autoantibody are recognized by macrophage Fcγ and complement receptors. This triggers phagocytosis and elimination of RBCs from the circulation by splenic macrophages. We recently found that CD47 on unopsonized RBCs binds macrophage signal regulatory protein α (SIRPα), generating a negative signal that prevents phagocytosis of the unopsonized RBCs. We show here that clearance and phagocytosis of opsonized RBCs is also regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
351
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 399 publications
(372 citation statements)
references
References 27 publications
15
351
1
5
Order By: Relevance
“…22,23 Indeed, we found that IgGopsonized CD47 Ϫ/Ϫ RBCs were phagocytosed 4 to 5 times more efficiently by RPM over a range of opsonization levels, compared with equally opsonized WT RBCs ( Figure 3A). To understand how CD47 regulates macrophage uptake of senescent RBCs, we next investigated phagocytosis of WT or CD47 Ϫ/Ϫ Ox-RBCs.…”
Section: Cd47 Does Not Inhibit Serum-dependent Macrophage Phagocytosimentioning
confidence: 87%
See 1 more Smart Citation
“…22,23 Indeed, we found that IgGopsonized CD47 Ϫ/Ϫ RBCs were phagocytosed 4 to 5 times more efficiently by RPM over a range of opsonization levels, compared with equally opsonized WT RBCs ( Figure 3A). To understand how CD47 regulates macrophage uptake of senescent RBCs, we next investigated phagocytosis of WT or CD47 Ϫ/Ϫ Ox-RBCs.…”
Section: Cd47 Does Not Inhibit Serum-dependent Macrophage Phagocytosimentioning
confidence: 87%
“…Recognition of the cell surface glycoprotein CD47 by the inhibitory receptor signal regulatory protein alpha (SIRP␣) inhibits phagocytosis of unopsonized RBCs, as well as IgG or complementopsonized RBCs, both in vivo and in vitro. [20][21][22][23] CD47 is highly expressed on RBCs, but ubiquitously expressed by most cells in the body, and can also negatively regulate phagocytosis of platelets and leukocytes. [24][25][26] The amount of CD47 on the cell surface regulates macrophage phagocytosis, since IgG-opsonized RBCs from CD47 ϩ/Ϫ mice (expressing about 50% of normal levels of CD47) are taken up faster than wild-type (WT) RBCs, but slower than CD47 Ϫ/Ϫ RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…6,9 CD47 on target cells interacts with SIRPa on macrophages and transmits a 'don't eat me' signal through SH2 domain-containing phosphatases, SHP-1 and -2, and results in the inhibition of target cell phagocytosis. 7,28,29 CD47 is expressed at lower levels on bone marrow resident hematopoietic stem cells (HSCs) than on circulating HSCs. However, when bone marrow HSCs were mobilized out of bone marrow, they upregulated CD47.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 CD47 interacts with signal regulatory protein-a (SIRPa), thrombospondin (TSP)-1 and -2 to mediate various cellular functions. 7,8 In particular, CD47 signaling through SIRPa inhibits the phagocytosis of CD47-expressing target cells by SIRPa-expressing macrophages. Anti-CD47 monoclonal antibodies inhibiting the interaction of CD47 and SIRPa promote the phagocytosis of tumor cells by macrophages, and also by monocytes and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…The CD47-SHPS-1 system has been shown to regulate a novel cell-cell communication system that is important in immunology and hematology. CD47 on red blood cells binds to SHPS-1 on macrophages, thereby inhibiting macrophage activation and phagocytosis [28,29]. The interaction of SHPS-1 with CD47 negatively regulates cellular responsiveness during T cell activation and during the induction of antigen-specific cytotoxic T lymphocytes by DC and monocytes [24,30].…”
Section: Introductionmentioning
confidence: 99%